THREE PRENYLATED FLAVONOIDS FROM MACARANGA PEARSONII MERR. - Eva Marliana; Tjitjik Sri Tjahjandarie; Mulyadi Tanjung (PROSIDING SEMINAR KIMIA, 2015)
Three prenylated flavonoids, 4’-O-methyl-8-isoprenyleriodictiol (1), 4’-O-methyl-8-isoprenylnaringenin (2) and lonchocarpol A (3) have been isolated from the leaves of Macaranga pearsonii Merr.. The structure of compounds have been elucidated based on its spectroscopic data, including UV, 1D and 2D NMR, and HREISMS spectra.